2017
DOI: 10.21303/2504-5695.2017.00306
|View full text |Cite
|
Sign up to set email alerts
|

The Elaboration of Cheese Masses of Therapeutic and Prophylactic Direction With Cryoadditive “Pumpkin”

Abstract: There was grounded the expedience of using cryopowder “Pumpkin” in the technology of sweet and salt cheese masses. The possibility of using cryopowder “Pumpkin” as a component of therapeutic and prophylactic cheeses masses was studied. The main factors of introduction of cryoadditive “Pumpkin” are: normative organoleptic properties of product and its daily norm. The production of cheese masses with cryoadditive “Pumpkin” provides their combination with sugar or salt. The use of cryoadditive “Pumpkin” needs pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The content of useful substances, included in the cryopowders, is 6-10 times larger than that in the canned fruits or vegetables. Cryopowders considerably enhance the biological value of food products, as well as improve their chemical composition [7]. Addition the cryopowders to butter and margarine makes it possible to prolong the storage duration by almost 4.0 times [6].…”
Section: Results Of Research Into Using the Cryopowder "Amaranth" In mentioning
confidence: 99%
See 1 more Smart Citation
“…The content of useful substances, included in the cryopowders, is 6-10 times larger than that in the canned fruits or vegetables. Cryopowders considerably enhance the biological value of food products, as well as improve their chemical composition [7]. Addition the cryopowders to butter and margarine makes it possible to prolong the storage duration by almost 4.0 times [6].…”
Section: Results Of Research Into Using the Cryopowder "Amaranth" In mentioning
confidence: 99%
“…It is known that cryopowders from edible plant raw materials contain a wide range of carbohydrates, pectin substances, as well as vitamins, amino acids, cellulose, polyphenol compounds [7].…”
Section: Discussion Of Results Of Using the Cryopowder "Amaranth" In mentioning
confidence: 99%
“…More details on the research methodology can be found in [11]. An important criterion in developing the formulation of sweet and salty curds was to find optimum ratios of ingredients in order to obtain the appropriate standard taste.…”
Section: Methodsmentioning
confidence: 99%
“…The problem of supplying the population with rational and balanced nutrition is very urgent today. Taking into account modern ecological conditions, a food ration of a human must contain natural biologically active substances, able to increase the resistance of the organism [8,9]. Creation of new food products with a target destination due to using biologically active supplements, as opposite to traditional ones, allows to prevent and to correct results of human diseases [10,11].…”
Section: Review Of the Problemmentioning
confidence: 99%